Filipinos in Rural Hawaii - Anderson, Robert N. (University of Hawai'i Press, 1984)
Filipino immigrants and their descendants who have lived in Hawaiʻi's plantation communities are the subjects of this thoughtful and social analysis. Here is an inside look at various facets of Filipino rural life-working conditions, courtship pattern, living patterns, living standards, celebrations, and even "chicken fighting." Over the last couple of decades, the plantation towns of Hawaiʻi have been dying. Fewer workers are needed as land is converted to other uses and as labor-efficient production techniques are developed. The displacement of people whose lives have been centered on the functional apparatus of the plantations is particularly distressing. As Hawaiʻi copes with the human problems, it is important to understand the history, social behavior, and values of Filipino plantation workers, some of whom now face substantial hardship. The author and his co-researchers studied three plantation towns in depth and examined in varying detail the lives of Filipino plantation residents on the islands of Kauaʻi, Oʻahu, Molokaʻi, and Hawaiʻi. In the course of collecting data, they taped and transcribed a number of conversations, some of which are included here. These voices add a lively counterpoint to the data and discussion. As time and events overcome the caretakers of the ethnic cultures of Hawai'i's plantations, the rural lifestyles of these communities may be forgotten. Books such as this will help to preserve their flavor and texture. Social scientists, scholars and students of ethnic studies, community leaders, and even the people described herein will find this a useful and informative study.